Ancora su poteri, relazioni, guerra nel regno di Ferrante d'Aragona studi sulle corrispondenze diplomatiche II - Russo, Alessio (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2020)
This volume has the same title of the one published in 2011. It collects a series of studies on the long reign of the second Trastàmara King of Naples, Ferdinand of Aragon (1458-1494), using mainly the great mass of information offered by diplomatic correspondences. The authors study some key events and protagonists of Italian history in the Quattrocento (the battle of Ponza, the condottiero Giacomo Piccinino, the journey of Lorenzo de' Medici to Naples, the war of Ferrara) and important topics about politics and political communication: the relations between the Crown, the society and the fiscal institutions; the use of italian language in the autograph letters written by Lluís Dezpuig, a catalan; the "queenship" of the duchess of Ferrara.